The family's presence in hospitals in pandemic time and the patient safety paradox - Tânia Correia; Maria Manuela Martins; Fernando Barroso (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction: Due to the pandemic by COVID-19, to ensure the safety of health care and to contain its transmission, restrictive measures were taken to keep families away from hospitalized patients. Such measures have implications. Objective: to analyze, from the speeches of nurses specialized in rehabilitation nursing (EEER), the advantages, disadvantages and contexts of the family's presence in hospitals, in the light of patient safety, in a pandemic context. Methodology: Qualitative interpretative study based on James Reason's risk model, conducted through semi-structured interviews with 6 EEERs chosen for convenience. Content analysis was performed using the Atlas.ti software. and Bardin's methodology. Results: 17 categories were identified, grouped according to the representation of the family in patient safety: 10 categories in the view of the family that potentiates security failures and 7 within the family as a security barrier. Discussion: The EEERs consider the presence of the family as very important for hospitalized patients and for safety care, however, their speeches show that their performance was strongly influenced by the view of the family as a potential disseminator of infection, demonstrating a more negative assessment than positive of this presence for the maintenance of this security, not always supported by the available evidence. Conclusion: Restrictive measures may be contributing to a setback in the provision of care centered on the hospitalized patient's family. However, there is a lack of data at the national level that allows us to understand whether families in Portugal represent a safety risk in hospitalized patients.